2021
DOI: 10.1108/jed-08-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Does it pay to be green? An exploratory analysis of wage differentials between green and non-green industries

Abstract: PurposeThis paper investigates the potential wage impacts of a shift to more environmentally sustainable production patterns.Design/methodology/approachThe empirical analysis is carried out using labour force survey data and interval regressions.FindingsEstimates at the individual level suggest that small wage differentials exist: individuals employed in green industries earn about seven per cent more than those working in non-green industries.Originality/valueTo date, very little is known about the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 30 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…After nearly three decades, this question is still a hot dispute in pro-environmental behavior literature (He and Filimonau, 2020;Leonidou et al, 2022;Nguyen et al, 2022b). Indeed, although the effects of cultural values and pro-environmental intentions and behaviors have been of interest to some scholars recently (Cong Doanh et al, 2021;He and Filimonau, 2020;Saracevic et al, 2022), these studies showed the different, and even contrasting results (Chwialkowska et al, 2020), several scholars emphasize that there is an existing knowledge gap regarding our understanding about how cultural values influence pro-environmental behaviors, and therefore call for more effort to develop the consistent theory of culture-environmentally friendly behavior research (Chwialkowska et al, 2020;Asgari Toorzani and Rassafi, 2022;Saracevic et al, 2022;Jackman and Moore, 2021;Nguyen et al, 2021;Tran and Huang, 2021). According to our best knowledge, even though several scholars have already provided empirical evidence with regard to the significant relationships between cultural values and a different range of pro-environmental behaviors (Sreen et al, 2018;Leonidou et al, 2022;He and Filimonau, 2020), no previous studies examine how cultural values can accelerate individuals' energy-saving behaviors as well as the role of cultural values in closing the energy-saving attitude-intention-behavior gap.…”
Section: Cultural Values and Energysaving Behaviors 647mentioning
confidence: 99%
“…After nearly three decades, this question is still a hot dispute in pro-environmental behavior literature (He and Filimonau, 2020;Leonidou et al, 2022;Nguyen et al, 2022b). Indeed, although the effects of cultural values and pro-environmental intentions and behaviors have been of interest to some scholars recently (Cong Doanh et al, 2021;He and Filimonau, 2020;Saracevic et al, 2022), these studies showed the different, and even contrasting results (Chwialkowska et al, 2020), several scholars emphasize that there is an existing knowledge gap regarding our understanding about how cultural values influence pro-environmental behaviors, and therefore call for more effort to develop the consistent theory of culture-environmentally friendly behavior research (Chwialkowska et al, 2020;Asgari Toorzani and Rassafi, 2022;Saracevic et al, 2022;Jackman and Moore, 2021;Nguyen et al, 2021;Tran and Huang, 2021). According to our best knowledge, even though several scholars have already provided empirical evidence with regard to the significant relationships between cultural values and a different range of pro-environmental behaviors (Sreen et al, 2018;Leonidou et al, 2022;He and Filimonau, 2020), no previous studies examine how cultural values can accelerate individuals' energy-saving behaviors as well as the role of cultural values in closing the energy-saving attitude-intention-behavior gap.…”
Section: Cultural Values and Energysaving Behaviors 647mentioning
confidence: 99%
“…To account for differences among industries and time periods, we add dummy variables representing industry and year into Model (1) (Jackman and Moore, 2021). This study uses FE estimations to examine the impact of epidemics on corporate CSR disclosure.…”
Section: Model Specification and Variablesmentioning
confidence: 99%
“…It is undisputed that global environmental issues, including climate change and global warming, determined as the leading threats to human society and civilization, are derived from extensive energy consumption (Bulunga and Thondhlana, 2018; Ghosh, 2022; Naik and Bagodi, 2021; Nguyen et al , 2022a). Although energy is considered one of the most important resources for economic growth (Hoang Ngoc and Hoang Quang, 2018; Jackman and Moore, 2021), its extensive consumption detrimentally affects the environment and seriously threatens the nation’s sustainable development goals (Ezzi et al , 2022; Fathima M.S et al , 2022; Vasilev, 2022). There is a sharp increase in energy demand in most countries around the world (Tran et al , 2022).…”
Section: Introductionmentioning
confidence: 99%